Gerakan Cinta Arsip Keluarga (Genta Siaga): Pionir Program Penataan Arsip Keluarga di Desa Indonesia - Sabita, Salma Dilsani; Susanti, Titi; Bramantya, Arif Rahman; Sholikhah, Faizatush (UI Scholars Hub, 2023)
The Library and Archival Department of Sleman Regency, as the organization responsible for the administration of archives in Sleman Regency, has an outreach program for organizing family records called Genta Siaga. The Genta Siaga Program began in 2016 and was carried out every year until 2019. This outreach program was carried out to increase the awareness of the Sleman community towards the arrangement of family records. This is because Sleman Regency itself is one of the disaster-prone areas. Therefore, this research was conducted to find out about Genta Siaga as a pioneer of the family records management program in Indonesia, the technical implementation,and the benefits that the community got after participating in this program. This research uses a descriptive qualitative approach and inductive theorization. The outreach program from the Library and Archival Department of Sleman Regency is the unit of analysis in this research. The method used in collecting data is observation, interview, and literature study. The data that has been obtained is then processed into information so as to obtain conclusions from the results of the study. The conclusion obtained from this research is that the Genta Siaga is a form of archiving for the community through outreach.Genta Siaga became a pioneer in the family records management program in Indonesia because it was implemented before the publications of the GNSTA regulations and the EMAS application. The stages of implementing the Genta Siaga Program itself include internal meetings, village meetings, the formation of cadres, socialization with cadres, socialization with the community, implementation, supervision, and evaluation. Village communities who have participated in these activities have also benefited from organizing family records, namely better arrangement of family records, safer family records, and the emergence of public awareness of disaster preparedness. However, there are still obstacles faced, including the difficulty of adjusting to the village community's time, the community's limited literacy, the condition of the records being damaged, and the budget limitations of the Library and Archival Department of Sleman Regency and the village government.